2011
DOI: 10.1007/s10291-010-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ZTD derived from ECMWF/NCEP data with GPS ZTD over China

Abstract: The accuracy and feasibility of computing the zenith tropospheric delays (ZTDs) from data of the European Center for Medium-Range Weather Forecasts (ECMWF) and the United States National Centers for Environmental Prediction (NCEP) are studied. The ZTDs are calculated from ECMWF/NCEP pressure-level data by integration and from the surface data with the Saastamoinen model method and then compared with the solutions measured from 28 global positioning system (GPS) stations of the Crustal Movement Observation Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 15 publications
(15 reference statements)
1
61
1
1
Order By: Relevance
“…Experiments show that RMS of the tropospheric delay residuals derived from the medium-range NWP model from the SMB are between 24.02 and 32.62 mm, which is much better than that of the ECMWF and NCEP shown in the research of Chen et al [28]. However, it should be mentioned that it is not completely fair to compare the ZTD residual of them as the spatial resolutions of them are different.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Experiments show that RMS of the tropospheric delay residuals derived from the medium-range NWP model from the SMB are between 24.02 and 32.62 mm, which is much better than that of the ECMWF and NCEP shown in the research of Chen et al [28]. However, it should be mentioned that it is not completely fair to compare the ZTD residual of them as the spatial resolutions of them are different.…”
Section: Discussionmentioning
confidence: 79%
“…Research demonstrated that the ZTD derived from the NWP model-global data acquisition system (GDAS) agreed with the IGS ZTD solutions at a 3.0 cm root mean square difference (RMSD) level with biases of up to 4.5 cm over a 1.5-year period at 18 globally distributed IGS stations [27]. The test results of [28] showed that the RMSD of the ZTD calculated by the European Centre for Medium-Range Weather Forecasts (ECMWF), reanalyzed data with a horizontal resolution of 0.5 • × 0.5 • in China, was 3.54 cm and that of the National Centers for Environmental Prediction (NCEP), with a horizontal resolution of 2.5 • × 2.5 • , was 5.36 cm. However, the tropospheric delay estimated by the reanalyzed data cannot be used in real-time positioning.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Conventionally, the total delay of GPS radio signals along the line of sight from each satellite are mapped to the zenith direction leading to a single average parameter called the zenith total delay or zenith path delay (ZPD). ZPD is a crucial parameter for meteorological and climatological study (Kuo et al 2000;Chen et al 2011). For instance, it serves as an additional input parameter in Numerical Weather Prediction (NWP) models for synoptic meteorology, while for nowcasting; it is a standard real time product used as a measure of the state of the atmosphere (Bosy et al 2010).…”
Section: Introductionmentioning
confidence: 99%